Hybrid quantum chemistry method for strongly correlated crystals containing transition metals - Popov, Ilya (2025)
This thesis presents the Effective Hamiltonian of Crystal Field (EHCF) method, a hybrid quantum chemical method developed for an accurate treatment of strongly correlated d-shells of transition metal atoms embedded into periodic systems. The main emphasis is made on the quantitative description of local d-d (crystal field) electronic transitions. EHCF is based on dividing a space of one-electron states in two subspaces separately spanned by d- and s,p-atomic orbitals. The many-electron wave function of the correlated d-system is expressed in the configuration interaction form, while the s,p-subsystem is described by the single-reference wave function. Resonance interactions between subsystems are considered by the Löwdin partitioning technique combined with the Green function formalism.